INNOVATIVE APPROACHES TO TEACHING AND ASSESSING FOREIGN LANGUAGES THROUGH THE CEFR FRAMEWORK (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article examines innovative approaches to foreign-language teaching and assessment within the Common European Framework of Reference for Languages (CEFR). As CEFR has become the most influential international standard for describing and measuring language proficiency, modern instruction increasingly relies on competency-based pedagogy, task-based learning models, digital assessment systems, and AI-driven feedback mechanisms. Through an analysis of theoretical foundations and practical applications, this article argues that CEFR descriptors enhance transparency, learner autonomy, and the reliability of evaluating communicative performance. At the same time, challenges such as teacher preparedness, contextual adaptation, and maintaining assessment validity in digital environments persist. The article concludes that CEFR-aligned innovations are essential for maintaining globally relevant and pedagogically sound language education.